Recent Advances in Biofertilizers and Biofungicides (PGPR) for Sustainable Agriculture - Reddy, M S; Ilao, Rodolfo I; Faylon, Patricio S; Dar, William D; Sayyed, Riyaz; Sudini, H; Kumar, K. Vijay Krishna; Armanda, Adoracian (Cambridge Scholars Publishing, 2014)
Global concern over the demerits of chemicals in agriculture has diverted the attention of researchers towards using the potential of PGPR in agriculture. This book contains many useful and important research papers pertaining to the use of bio-fertilizers and bio-fungicides for sustainable agriculture. This volume is presented in an easy-to-understand manner,with well-illustrated protocols on the production to commercialization of PGPR. The chapters on commercial potential, trade and regula.